EMPOWERING POSYANDU CADRES UTILIZING EDUCATIONAL MEDIA FOR THE ELDERLY AT TEMINDUNG SAMARINDA: PEMBERDAYAAN KADER POSYANDU DALAM MEMANFAATKAN MEDIA EDUKASI LEMBAR BALIK UNTUK LANSIA DI TEMINDUNG, SAMARINDA - Anif Muchlashin; Kamilah Dwi Kurniawati; Purwaningsih Purwaningsih (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Temindung Village, Samarinda City, has difficulty implementing Posyandu stands for ‘Pos Pelayanan Terpadu’ in Bahasa, meaning ‘Integrated Service Post’, especially in providing Integrated Health Program (IHP). Difficulties faced include limited cadre’s capacity, scheduling overlap among individuals of different ages, low participation from adolescents and senior citizens, and a lack of educational media. Objective: This activity will improve cadre’s skills in providing health services using learning media and increase community involvement in IHP activities. Method: The activities included the distribution of learning media, such as leaflets, posters, and flipcharts, to toddlers, adolescents, and elderly citizens. Activities were done directly with cadres using participatory and educational methods. Evaluations were done through implementation monitoring and observations of changes in skills among cadres and community involvement. Results: The program successfully helped cadres deliver services in a clearer, more interactive manner, resulting in a 14% increase in post-test scores. The use of educational media increased public understanding and interest, with an average post-test score of 89, resulting in increased participation among youth and seniors. Conclusion: The program contributed to the success of Posyandu implementation.